Effects of fluconazole on the pharmacokinetics of celecoxib and its carboxylic acid metabolite in different CYP2C9 genotypes - Cho, Chang-Keun; Kang, Pureum; Jang, Choon-Gon; Lee, Yun Jeong; Bae, Jung-Woo; Choi, Chang-Ik; Lee, Seok-Yong (Archives of pharmacal research, 2025)
This study aimed to investigate the effects of fluconazole, a moderate inhibitor of CYP2C9 and CYP3A4, on the pharmacokinetics of celecoxib and its carboxylic acid metabolite in different CYP2C9 genotypes. A total of thirty-nine healthy Korean male volunteers were divided into three different CYP2C9 genotype groups ( CYP2C9*1/*1 , *1/*3 and *3/*3 genotypes) and were enrolled in the celecoxib alone trial, celecoxib with fluconazole trial, or both. In the celecoxib alone trial, participants received a single oral dose of 200 mg celecoxib. In the celecoxib with fluconazole trial, participants received 300 mg fluconazole on day 1, 150 mg fluconazole once daily for four consecutive days (day 2–5), and a coadministration of 200 mg celecoxib with 150 mg fluconazole on day 6. Plasma concentrations of celecoxib and celecoxib carboxylic acid were determined by using HPLC–MS/MS. In the CYP2C9*1/*1 genotype group, fluconazole treatment increased AUC inf of celecoxib by 2.61-fold, and decreased CL/F by 60.4% (both p < 0.001). In the CYP2C9*1/*3 genotype group, fluconazole treatment increased AUC inf of celecoxib by 2.44-fold (p < 0.001), prolonged t 1/2 by 1.36-fold (p < 0.05), and decreased CL/F by 60.4% (p < 0.001). Fluconazole treatment increased AUC inf of celecoxib by 2.23-fold, prolonged t 1/2 by 1.64-fold, and decreased CL/F by 53.8% in the subject with CYP2C9*3/*3 genotype. C max of celecoxib carboxylic acid significantly decreased in CYP2C9*1/*1 and *1/*3 genotypes (p < 0.01 and p < 0.05, respectively), following fluconazole treatment, whereas AUC inf showed no significant changes in any CYP2C9 genotype group. In conclusion, fluconazole affected the pharmacokinetics of celecoxib in different CYP2C9 genotypes.